Parliamentary debates, House of Commons, Monday, 27th November, 1911 : official report, contents: Great Britain and Germany, Sir Edward Grey's statement. (London : His Majesty's Stationery Office, 1911)
Bibliotheek Camille Huysmans
Engels
Monografie
Keywords: internationale politiek; Groot-Brittannië.; Duitsland